PENERAPAN SISTEM LAPORAN KEUANGAN BULANAN PADA PERUSAHAAN MULTI LEVEL MARKETING PT K-LINK INDONESIA MOBILE STOCKIS DI TIMIKA - Suryani Dinda Lestari Tarantein; Daniel Nemba Dambe (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
This research aims to determine the application of the monthly financial reporting system to multi-level marketing companies at PT K-Link Indonesia mobile stockists in Timika. This research is a descriptive research. The descriptive method used is the document research method used to collect data, record, and obtain information from archives or documents related to research. Documentation of various documents related to research, and literature, namely collecting data through books to obtain data and theoretical concepts. To compile the financial statements of PT K-Link Indonesia mobile stockists, the steps used are collecting transaction evidence, making journals, making ledgers, making a trial balance, making adjusting journals, and making profit and loss statements. To find out the ability of PT K-Link Indonesia mobile stockists in comply the profits used profitability ratios. The results of this study indicate that the application of the monthly financial reporting system to multi-level marketing companies of PT K-Link Indonesia mobile stockists in Timika has not followed the applicable SAK (Financial Accounting Standards). With the existence of a financial report system created by the author based on profitability ratios, the company can find out the company's ability to sell. In the Indonesia mobile stock-link PTK in Timika that in the calculation using the profitability ratio can be concluded that the monthly financial statements of the company are said to be good. Because the results of gross profit margins (gross profit margins), net profit margins (net profit margins), return on investments (ROI) and return on equity (ROE) in the Indonesian mobile PT K-link company stockis Timika showed the percent of profits achieved by sell products.